Physical activity and the link among stress, burnout, and well-being in athletic trainers - Pacewicz, C. E.; Rowley, T. W.; Savage, J. L. (Journal of Athletic Training, 2023)
Context Stress is a leading cause of burnout in working professionals, including athletic trainers (ATs). One consequence of burnout for ATs is lower perceptions of well-being, which have implications for mental and physical health. Physical activity is known to help reduce stress. Thus, activity may help reduce stress and burnout in ATs while enhancing well-being.